(untitled) (Journal of Computational Mathematics, 1984)
In this paper, we introduce a method of numerical integration on a polytope of multiple dimensions. Its basic idea is to cut a polytope into some simplices and sum the integral values on the simplices. We give the integral formulae, the expressions to estimate the error and the method for cutting a polytope into simplices. Some examples are provided to explain the adaptability of the method.